A Panel Data Analysis for Evaluating the Profitability of the Banking Sector in Bangladesh - Abedin, Md. Thasinul; Dawan, Md. Muzammel (Asian Journal of Economics and Empirical Research, 2016)
This study attempts to evaluate the profitability for a panel of 29 listed commercial banks of Bangladesh. Panel GMM approach along with Pooled OLS and Random Effect OLS has been applied to discover the impact of key factors namely investment in government securities and shares, loan and advances, human resource, efficiency, and economy money supply growth on profitability using the data set from 2005-2015 for each bank. The study has found that loan and advances, human resource, efficiency, and economy money supply growth have significant positive impact on profit where investment in government securities and shares has significant negative impact. Therefore, more loan and advances, more human resource, more efficiency, and more money supply growth unlike investment in government securities and shares will eventually boost up the profitability of banks.